1995
DOI: 10.1083/jcb.130.5.1171
|View full text |Cite
|
Sign up to set email alerts
|

A 39-kD DNA-binding protein from mouse brain stimulates transcription of myelin basic protein gene in oligodendrocytic cells.

Abstract: Abstract. The MB1 regulatory sequence of the myelin basic protein (MBP) gene spanning between nucleotides -14 to -50 with respect to the transcription start site is critical for cell type-specific transcription of the MBP gene, which encodes the major protein component of myelin sheath in cells derived from the central nervous system (CNS). This regulatory sequence has the ability to interact with a developmentally controlled DNA-binding protein from mouse brain that stimulates transcription of MBP promoter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
91
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 46 publications
4
91
1
Order By: Relevance
“…21 Expression of the PURA gene has been observed in all tissues analyzed, and the protein is highly conserved across several species. [22][23][24] Pur␣ has been implicated in control of DNA replication, 22,25,26 and it has been reported to be a transcriptional activator of both viral 27 and mammalian 23,28,29 promoters.…”
Section: Introductionmentioning
confidence: 99%
“…21 Expression of the PURA gene has been observed in all tissues analyzed, and the protein is highly conserved across several species. [22][23][24] Pur␣ has been implicated in control of DNA replication, 22,25,26 and it has been reported to be a transcriptional activator of both viral 27 and mammalian 23,28,29 promoters.…”
Section: Introductionmentioning
confidence: 99%
“…In human cells both p107 (Devoto et al, 1992) and p130 (Hannon et al, 1993) may be found in complexes with Cyclin A and CDK2, proteins now believed to associated with Pura (Itoh et al, 1998). In addition to its e ects on DNA replication, several recent reports have now established Pura as a transcription factor (Chepenik et al, 1998;Du et al, 1997;Haas et al, 1995;Herault et al, 1992Herault et al, , 1993Kelm et al, 1997;Krachmarov et al, 1996;Zambrano et al, 1997). It is quite conceivable that changes in gene expression could result from changes in Pura levels during the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Pura is a 322 amino acid sequence-speci®c singlestranded DNA-binding protein implicated in the control of both DNA replication and gene transcription Du et al, 1997;Haas et al, 1995;Kelm et al, 1997;Zambrano et al, 1997). Structurally, the central region of Pura is composed of three 23 amino acid class I repeats interspersed with two 26 amino acid class II repeats .…”
mentioning
confidence: 99%